Pengenalan Lapangan Persekolahan I Di SMA Negeri 2 Palangka Raya Oleh Mahasiswa Prodi PBSI Universitas Palangka Raya - Misnawati Misnawati; Linggua Sanjaya Usop; Ratna Lisa; Rania Rania; Lisa Lisa (Universitas 45 Surabaya, 2023)
Introduction to School Field Experience (PLP I) is a process of observation and internship conducted by undergraduate education students to study the aspects of teaching and educational management in educational institutions, which is essential for students. This activity aims to familiarize each student with the atmosphere and activities of schooling through direct observation in relevant schools. The objectives of this activity are to develop education majors' competencies in academic education and their specific field of study, to understand the teaching and learning environment directly in a school setting, and to prepare students to understand and embrace their future profession. Observation activities are carried out through direct observation. The aspects observed during direct observation include: (1) school culture, (2) school organizational structure and governance, (3) school vision and mission, (4) co-curricular and extracurricular activities, (5) school rules and regulations, (6) ceremonial-formal activities, and (7) positive behavioral practices.